The added diagnostic value of postreflux swallow‐induced peristaltic wave index and nocturnal baseline impedance in refractory reflux disease studied with on‐therapy impedance‐pH monitoring. Issue 3 (12th September 2016) - Frazzoni, M.; de Bortoli, N.; Frazzoni, L.; Tolone, S.; Furnari, M.; Martinucci, I.; Mirante, V. G.; Marchi, S.; Savarino, V.; Savarino, E.
Abstract: Background: On‐therapy impedance‐pH monitoring in proton pump inhibitor (PPI)‐refractory gastroesophageal reflux disease (GERD) yielded conflicting results. We aimed to assess the diagnostic value of postreflux swallow‐induced peristaltic wave (PSPW) index and mean nocturnal baseline impedance (MNBI) in PPI‐refractory heartburn. Methods: On‐therapy impedance‐pH tracings from 189 consecutive patients with PPI‐refractory heartburn were blindly reviewed. Patients were subdivided into refractory reflux esophagitis (RRE), healed reflux esophagitis (HRE), non‐erosive reflux disease (NERD), and functional heartburn (FH) according to endoscopic and conventional impedance‐pH findings. The diagnostic accuracy of PSPW index and MNBI in separating NERD from FH was assessed with receiver‐operating‐characteristic (ROC) analysis. Objectively documented persistent reflux remission at 3‐year follow‐up in 53 patients who underwent laparoscopic fundoplication served to evaluate PSPW index and MNBI as independent predictors of PPI‐refractory GERD confirmed by positive surgical outcome. Key Results: Median PSPW index and MNBI values were significantly lower in 39 RRE (16%; 1145 Ω) than in 41 HRE (25%; 1741 Ω) and in 68 NERD (29%; 2374 Ω) patients, and in all three GERD subgroups compared to 41 FH cases (67%; 3488 Ω) ( P <.008). At ROC analysis, comparing NERD to FH the area under the curve was 0.886 with PSPW index and 0.677 with MNBI ( P =.005). PSPW index was an independent predictor of PPI‐refractory GERD (odds ratio 0.6983, P =.012). Conclusions & Inferences: At on‐therapy impedance‐pH monitoring, PSPW index and MNBI efficiently distinguish PPI‐refractory NERD from FH. The PSPW index represents an independent predictor of PPI‐refractory GERD. Abstract : On‐therapy impedance‐pH monitoring establishes the relationship between PPI‐refractory heartburn and reflux. Post‐reflux swallow‐induced peristaltic wave (PSPW) index and mean nocturnal baseline impedance (MNBI) were highly efficient in distinguishing PPI‐refractory non‐erosive reflux disease (NERD) from functional heartburn (FH) and refractory reflux esophagitis (RRE) from healed reflux esophagitis (HRE). Abnormal PSPW index and MNBI characterize reflux‐related PPI‐refractory heartburn.